Jmjd3/IRF4 axis aggravates myeloid fibroblast activation and m2 macrophage to myofibroblast transition in renal fibrosis - Liang, Hua; Liu, Benquan; Gao, Ying; Nie, Jiayi; Feng, Shuyun; Yu, Wenqiang; Wen, Shihong; Su, Xi (Frontiers in Immunology, 2022)
Renal fibrosis is a common pathological pathway of progressive chronic kidney disease. Here, we explored the role of Jumonji domain containing 3 (Jmjd3)/interferon regulatory factor 4 (IRF4) axis in myeloid fibroblasts activation and M2 macrophages to myofibroblasts transition (M2MMT) in renal fibrosis. In mice, Jmjd3 and IRF4 were highly induced in interstitial cells of kidneys with folic acid or obstructive injury. Targeted inhibition of Jmjd3 with myeloid-specific genetic deletion or Jmjd3 inhibitor reduced the levels of IRF4 in injured kidneys. Myeloid Jmjd3 depletion impaired bone marrow-derived fibroblasts activation and M2MMT in folic acid or obstructive nephropathy, resulting in reduction of extracellular matrix proteins expression, myofibroblasts formation and renal fibrosis progression. Pharmacological inhibition of Jmjd3 also prevented myeloid fibroblasts activation, M2MMT, and kidney fibrosis development in folic acid nephropathy. Furthermore, IRF4 disruption inhibited myeloid myofibroblasts accumulation, M2MMT, extracellular matrix protein production, and displayed much less fibrosis in obstructed kidneys. Finally, wild-type mice engrafted with IRF4-/- bone marrow cells presented fewer myeloid myofibroblasts in the kidneys and exhibited less severe renal fibrosis following obstructive injury compared with wild-type mice engrafted with IRF4+/+ bone marrow cells. Myeloid Jmjd3 deletion or Jmjd3 inhibitor attenuated expressions of IRF4, α-smooth muscle actin and fibronectin and impeded M2MMT in cultured monocytes exposed to IL-4. Thus, Jmjd3/IRF4 signaling has a crucial role in myeloid fibroblasts activation, M2 macrophages to myofibroblasts transition, extracellular matrix protein deposition, and fibrosis progression.